The Effectiveness Of The SQ3R (Survey, Question, Read, Recite, Review) Lerning Model Combined With Reading Literacy On Critical Thinking Skills - suarti, suarti; Rusmin, Muhammad; Ramadhani , Andi Rezki Awliah (Al-Khazini: Jurnal Pendidikan Fisika, 2023)
This study aims to determine the level of critical thinking skill of students who are taught with the SQ3R learning model (Survey, Question, Read, Recite Review) and conventional learning models combined with reading literacy, knowing the differences in critical thinking skills of students who are taught with SQ3R learning model (Survey, Question, Read, Recite Review) and those taught with conventional learning models combined with reading literacy and to find out the effectiveness of the SQ3R learning model combined with reading literacy on critical thinking skills. This research is a type of quasi-experimental research, with a Nonequivalent Control Group research design. The sample of this study was students at SMAN 1 Maros consisting of two classes selected using a purposive sampling technique, namely class XI IPA 2 as the control class and class XI IPA 3 as an experimental class. The instruments used are tests of critical thinking skills, observation sheets and questionnaires. The data analysis technique used is descriptive data analysis, the mean difference test with the independent sample t-test and the N-Gain test. The results showed that the average critical thinking ability of students in the experimental class was 36.64 in the pre-test and 79.80 in the post-test while for the controller class, the value of the pre-test was 41.09 and the post-test was 79.53. From the average pre-test to post-test results in the experimental class increased by 43.16 while the control class increased by 38.44. The results of the average difference test for critical thinking skills obtained a significance of 0.001 < 0.05, which means that there is a significant difference in critical thinking skills between the experimental class and the control class. From the results of the N-gain test for the experimental class it was 67 in the quite effective category and for the controller class it was 65 in the quite effective category. Thus, from the results of data analysis, it can be concluded that the use of the SQ3R model (Survey, Question, Read, Recite Review) combined with reading literacy is quite effective in increasing critical thinking skills.